Effectiveness of pelvic circumferential compression device for lower body trauma: Insights from a Japan Trauma Data Bank retrospective study - Shohei Ono; Satoshi Miyata; Hiroaki Suzuki; Keiki Shimizu (Acute Medicine & Surgery)
Abstract Aim Pelvic ring fractures (PRFs) due to high‐energy trauma often result in severe bleeding and high mortality. Pelvic circumferential compression devices (PCCD) are widely used to stabilize PRF and decrease bleeding. However, evidence supporting their effectiveness is still inconclusive. Methods We conducted an observational study using the Japan Trauma Data Bank (JTDB) from 2019 to 2021. Patients with blunt lower body trauma aged 15 years or older were included. We used propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) to evaluate the association of PCCD and mortality. Results Of the 74,393 patients in the database, 235 PCCD group and 23,429 control group were analyzed. After PSM, 231 patients in both groups were enrolled. Crude analysis indicated significantly higher in‐hospital mortality in the PCCD group (odds ratio (OR) = 3.8 [95% CI = 2.51–5.75]). However, PSM and IPTW analysis indicated that PCCD was associated with decreased in‐hospital mortality (PSM: OR = 0.79 [0.43–1.42]; IPTW: OR = 0.73 [0.62–0.86]). In a subgroup analysis of the IPTW analysis, PCCD fitting resulted in increased in‐hospital mortality in the group without PRF (OR = 2.08 [1.91–2.27]), a decrease in stable PRF (OR = 0.74 [0.6–0.91]), and a further decrease in unstable PRF (OR = 0.18 [0.12–0.27]). Additional factors, such as a fall from a height, a fall downstairs, and pre‐hospital PCCD placement also influenced the treatment effect. Conclusion The present, large, registry‐based study found that PCCD reduced mortality in patients with a lower body injury, especially those with an unstable PRF.